BE_ZIVILSTRAF BK 2023 173 vom 21. November 2023 - BE Obergericht (2023)
indemnité (non-entrée en matière) ; procédure pénale pour insoumissions à une décision de l'autorité | Einstellung/Nichtanhandnahme